USING “THE ADD A WORD” GAME IN TEACHING GRAMMAR TO JUNIOR HIGH SCHOOL STUDENTS - Fauza Fauza; Don Narius (Journal of English Language Teaching, 2013)
This article was written to describe the implementation of “The Add a Word” game in teaching grammar to junior high school students. The ability of junior high school students in learning grammar is low. Because they think that learning grammar is difficult and get bored. Because of that teacher should find an appropriate way that can attract students’ interest in learning grammar. One of an appropriate way is by using “The Add a Word” game. In this game teacher ask students to make one sentence, but everybody just say one word. The teacher gives a topic, then first student say one word, next student continue the sentence by saying one word.  Abstrak Artikel ini ditulis untuk menjelaskan bagaimana cara menerapkan pengajaran tata bahasa kepada siswa sekolah menengah pertama dengan permainan “The Add a Word”. Kemampuan siswa menengah pertama dalam memahami tata bahasa inggris masih sangat kurang. Ini disebabkan karena mereka menganggap belajar tata bahasa itu sulit dan membosankan. Untuk itu guru harus dapat menggunakan cara yang tepat agar siswa nyaman dalam belajar tata bahasa. Salah satu cara yang cocok adalah dengan menggunakan “The Add a Word” game. Pada permainan ini siswa disuruh membuat kalimat tapi setiap siswa hanya mengucapkan satu kata saja. Guru memberikan satu topik, lalu siswa pertama memulai dengan satu kata, siswa seterusnya melanjutkan dengan satu kata juga untuk melanjutkannya.